“Using National Games to Enhance Visual Literacy and Creativity in Primary School Students” - Xidoyeva Mahliyo Bozor qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the pedagogical value of national games in enhancing visual literacy and creativity among primary school students. It highlights how integrating traditional games into art lessons can foster compositional thinking, emotional expression, and cultural awareness. The study also provides practical strategies for teachers to make lessons more engaging and effective.